Segmentation and Statistical Processing of Geometric and Spatial Data on Self-Organized Surface Relief of Statically Deformed Aluminum Alloy; Applied Mechanics and Materials; Vol. 770 : Urgent Problems of Up-to-Date Mechanical Engineering - Lytvynenko I.; Maruschak P.; Lupenko S.; Panin S. V. Sergey Viktorovich (Materials Science in Mechanical Engineering, 2015)
Title screen